Monetary policy independence and the strength of the global financial cycle - Christian Friedrich; Pierre Guérin; Danilo Leiva-Léon (Bank of Canada, 2020)
We propose a new strength measure of the global financial cycle by estimating a regimeswitching factor model on cross-border equity flows for 61 countries. We then assess how the strength of the global financial cycle affects monetary policy independence, which is defined as the response of central banks' policy interest rates to exogenous changes in inflation. We show that central banks tighten their policy rates in response to an unanticipated increase in the inflation gap during times when global financial cycle strength is low. During times of high financial cycle strength, however, the responses of the same central banks to the same unanticipated changes in the inflation gap appear muted. Finally, by assessing the impact of different policy tools on countries' sensitivities to the global financial cycle, we show that using capital controls, macroprudential policies, and the presence of a flexible exchange rate regime can increase monetary policy independence.
Keywords: F32; E4; E5; G15; F42; G18; 330; Monetary policy; Exchange rate regimes; Financial system regulation and policies; International financial markets; Business fluctuations and cycles